2012
DOI: 10.5267/j.ccl.2012.6.001
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective one-pot, three component synthesis of ethyl 6-aryl-3-propylpyridazine-4-carboxylates in water

Abstract: A regioselective synthesis of ethyl 6-aryl-3-propylpyridazine-4-carboxylates by one-pot threecomponent reaction of ethyl butyrylacetate with various arylglyoxals in the presence of hydrazine hydrate at room temperature in water was described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…Consequently, MCRs have emerged as a powerful tool for delivering molecular libraries needed in combinatorial approaches for the assembly and lead identification of bioactive compounds. [21] Based on the above considerations and in continuance of our previous research into the arylglyoxal-mediated synthesis of various heterocycles, [22][23][24][25][26][27][28][29][30][31][32] we have found that 1,3-dialkyl thiobarbituric acids undergo a tandem Knoevenagel-Michael condensation with arylglyoxals leading to the formation of a substituted pyranopyrimidine skeleton. Herein, we report an efficient two-component strategy for synthesis of symmetrically substituted 5-aryloyl-1H-pyrano[2,3-d]pyrimidine 1.…”
Section: Introductionmentioning
confidence: 95%
“…Consequently, MCRs have emerged as a powerful tool for delivering molecular libraries needed in combinatorial approaches for the assembly and lead identification of bioactive compounds. [21] Based on the above considerations and in continuance of our previous research into the arylglyoxal-mediated synthesis of various heterocycles, [22][23][24][25][26][27][28][29][30][31][32] we have found that 1,3-dialkyl thiobarbituric acids undergo a tandem Knoevenagel-Michael condensation with arylglyoxals leading to the formation of a substituted pyranopyrimidine skeleton. Herein, we report an efficient two-component strategy for synthesis of symmetrically substituted 5-aryloyl-1H-pyrano[2,3-d]pyrimidine 1.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, pyridazines are useful intermediates in the construction of several other heterocycles [16,17]. With all the above facts in mind and as a part of our program directed towards the synthesis of polyfunctionalized substituted 5-heterocyclo-8-hydroxyquinolines of potential biologically interest [18][19][20][21][22], we have devoted some efforts to the construction of a novel ethyl 6-(8-hydroxy quinolin-5-yl)-3-methylpyridazin-4-carboxylate (4) as a conveniently accessible precursor for the synthesis of some hitherto unreported substituted 8-quinolinolinyl-5-pyridazines and their related derivatives in one-pot three component environ-mental friendly method [23]. 5-Acetyl-8-hydroxyquinoline (1) (2.21 g, 10 mmol) and SeO2 (5.55 g, 50 mmol) were dissolved in a mixture of dioxane (80 mL) and water (5 mL) and refluxed for 8 h. After filtration of the black selenium powder, the clear filtrate as concentrated nearly to dryness.…”
Section: Introductionmentioning
confidence: 99%
“…Algunas metodologías requieren un exceso de reactivos que luego es necesario recuperar (Coates, et al,1993) o usan sistemas de calentamiento convencional (Bel Abed, et al, 2012); sin embargo, el gran potencial fármaco-biológico de este tipo de sistemas ha hecho que se despierte el interés en diseñar metodologías nuevas y más eficientes, por ello se han estudiado metodologías alternativas a la clásicas, como es el caso de las reacciones "one pot" (reacciones secuenciales o reacciones en cascada) (Khalafy et al, 2013), que junto con la radiación de microondas (MW) ( (Dandia et al, 2006) proporcionan una interesante solución, ya que su implementación reduce considerablemente los tiempos de reacción, mejoran los rendimientos (Kaur 2015) con gran selectividad y especificidad y son más amigables con el medio ambiente (Majumder et al, 2013). Actualmente el uso de la tecnología de microondas se ha incrementado en los diferentes campos de la ciencia, por ejemplo, se conoce su aplicación en la extracción de productos naturales (Torrenegra et al, 2015) y particularmente en síntesis orgánica en condiciones libre de disolvente (Martins et al, 2009), ya que las reacciones son más simples, menos contaminantes y sobre todo con tiempos de reacción más cortos.…”
Section: Introductionunclassified
“…Las reacciones "one pot" son reacciones donde otro reactivo, mediador o catalizador es añadido después de la primera transformación, sin aislar el primer producto formado; es decir, reacciones en las que los distintos pasos de la secuencia sintética se realizan en diferentes condiciones de reacción (por ejemplo a diferentes temperaturas) y posteriormente sin necesidad de aislar los productos formados adicionar un nuevo reactivo o catalizador para finalmente, sin importar el número de etapas, obtener el producto de interés (Khalafy et al, 2013). Este trabajo se ha enfocado en la síntesis de moléculas con estructuras 6-aril-piridazin-3(2H)-ona que representan, como se ha mencionado, un núcleo importante con un amplio perfil farmacológico que incluye actividad vasodilatadora, un ejemplo son los medicamentos conocidos como Zardaverina, Levosimendan y motapisone (George y Saleh 2016).…”
Section: Introductionunclassified